National interests in an age of global technology - Lee, Thomas H., 1923-2001; Reid, Proctor P. (Series on prospering in a global economy., 1991)
U.S. policymakers must come to terms with the implications of the "globalization of technology"--Specifically, the dramatic increase in crossborder technical activities of private corporations and the rapid growth and redistribution of global technical capabilities since the mid-1970s. This book presents a policy framework for reconciling our national interests with the realities of the emerging global technical enterprise. Specific recommendations address how public policies can help ensure that U.S. citizens derive a fair share of the benefits of the global technology base. The volume discusses corporate nationality and its relevance to the policy debate, the need for greater international policy cooperation and negotiation in antitrust law, and the obligations of multinational corporations and their home and host governments. It also includes a series of detailed, up-to-date "technology profiles" of eight global industries, from aircraft engines to semiconductors.